Improving the Development of Student's Research Questions and Hypotheses in an Introductory Business Research Methods Course - Laurie Strangman; Elizabeth Knowles (International Journal for the Scholarship of Teaching and Learning, 2012)
In an introductory research methods course, students often develop research questions and hypotheses that are vague or confusing, do not contain measurable concepts, and are too narrow in scope or vision. Because of this, the final research projects often fail to provide useful information or address the overall research problem. A Lesson Study approach was used to develop a new lesson that models the development of research questions and hypotheses and provides multiple opportunities for students to practice this skill. Two tools were also developed to help students navigate this process, and the learning outcomes of the lesson were clearly defined. To assess the effectiveness of this lesson 122 research proposals generated by student research teams before and after implementation of the new lesson were evaluated using a grading rubric based on the learning outcomes. There were statistically significant improvements in three of the five learning outcomes.